Analisis Multimodal Terhadap Poster “8 Produk Israel yang di Boikot dan Alasannya” yang di Terbitkan oleh CNBC Indonesia - Kartiko, Yudistira Bayu (Program Studi Magister Linguistik Terapan UNJ, 2024)
The feud between Palestine and Israel still occurs today. This led to a boycott of Israeli products, which was aimed at showing resistance to what Israel was doing to Palestine. Apart from that, in Indonesia, there are many influencers and mass media who also report on events that occurred in Palestine. This is done in various ways, one of which is by creating poster designs about products originating from Israel. Analysis can be carried out from these posters to find out the ideology and implied meaning of the poster. So this is interesting to research. In this study, researchers used multimodal analysis as an analytical tool and also used a qualitative approach to present the results of the analysis that had been carried out. This research aims to find out the implied meanings in the posters and also look at the ideology of the poster maker. From the results of the analysis of the poster entitled